VeggieTales. The ballad of Little Joe [videorecording (DVD)] (Universal Pictures Home Entertainment, 2019)
The story of Joseph told in a Wild West version with Larry the Cucumber as the title character. Follow Little Joe's journey as his faith is tested every step of the way.